A National Study of Exemplary Writing Methods Instructors' Course Assignments. Issue 2 (3rd April 2019) - Scales, Roya Q.; Tracy, Kelly N.; Myers, Joy; Smetana, Linda; Grisham, Dana L.; Ikpeze, Chinwe; Yoder, Karen Kreider; Sanders, Jenn
ABSTRACT: In response to the dearth of research on K to 6 teacher preparation for teaching writing, we investigated writing methods course instructors' course assignments. Participants' courses met the following criteria: (a) Courses taken by undergraduate elementary teacher candidates; (b) Writing methods courses; (c) Use of exemplary writing instructional practices; and (d) Direct writing instruction with field application opportunities. Cross-case analysis revealed that despite vastly different teacher preparation programs and contexts, assignments were highly similar and focused on developing the candidates' self as writer or on becoming a teacher of writing. Assignments highlighted in the findings illuminate how exemplary writing methods course instructors support candidates' development and may be applied to programs seeking to create or to strengthen a writing methods course. Future directions for research are explored.